2018
DOI: 10.3390/molecules23071721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Ruthenium Schiff Base Complex on Glucose Homeostasis in Diet-Induced Pre-Diabetic Rats

Abstract: Pre-diabetes is a condition that precedes type 2 diabetes mellitus (T2DM) that is characterised by elevated glycated haemoglobin (HbA1c). The management of pre-diabetes includes the combination of dietary and pharmacological interventions to increase insulin sensitivity. However, poor patient compliance has been reported with regard to dietary interventions, therefore, new alternative drugs are required that can be effective even without the dietary intervention. In our laboratory, we have synthesised a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…46,47 Moreover, OA has also been reported to reduce the risk of developing cardiovascular disease by lowering LDL-C particles while increasing high-density lipoprotein cholesterol (HDL-C) particles. 16,17 These findings correlated with the previous study that reported that derivatives of OA such as 3-acetyl-oleanolic acid have also been shown to lower intrahepatic total cholesterol (TC), TGs and macrovesicular steatosis in high-fat diet-fed rats. 16,18,48 While the observed decrease in plasma TGs and VLDLs may partly be attributed to dietary intervention, it may also be ascribed to the insulinsensitizing effects of OA.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…46,47 Moreover, OA has also been reported to reduce the risk of developing cardiovascular disease by lowering LDL-C particles while increasing high-density lipoprotein cholesterol (HDL-C) particles. 16,17 These findings correlated with the previous study that reported that derivatives of OA such as 3-acetyl-oleanolic acid have also been shown to lower intrahepatic total cholesterol (TC), TGs and macrovesicular steatosis in high-fat diet-fed rats. 16,18,48 While the observed decrease in plasma TGs and VLDLs may partly be attributed to dietary intervention, it may also be ascribed to the insulinsensitizing effects of OA.…”
Section: Discussionsupporting
confidence: 87%
“…23 Recent studies in our laboratory have reported that prolonged consumption of a high-fat high-carbohydrate (HFHC) diet leads to the development of prediabetes. 17 This condition is characterized by complications including hypertriglyceridemia, insulin resistance and hyperinsulinemia which are risk factors for the development of NAFLD. 16,24 The conventional management of NAFLD involves the combination of insulin sensitizers and lifestyle modification therapy which include exercise and dietary modification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations